TEST ACTIVITIES SOME COMPOUNDS OLIGORESVERATROL RESULT OF INSULATION OF SKIN HOPEA ODORATA PLANT AS PREVENT 2-DEOKSIRIBOSE DEGRADATION - Atun, Sri (Jurnal Penelitian Saintek, 2010)
The objective of the study were measured inhibitory of 2-deoxyribose degradation activity of balanocarpol (1), ampelopsin H (2), hopheaphenol (3), and hemlesyanol C (4) which are resveratrol compounds from isolation of stem bark of Hopea odorata, and to study of different activity as 2-deoxyribose degradation activity from this compounds. Methods of this study to measured 2-deoxyribose degradation activity test with Fenton reaction method. Activity of 2-deoxyribose degradation activity calculated as percentage absorbansi decreased sample with bioactive compounds compared with a blank. As positif control used vitamin C and BHT (Butylated Hydroxy Toluena). The result of this study showed activity each compounds as 2-deoxyribose degradation activity of balanocarpol (1), ampelopsin H (2), hopheaphenol (3), and hemlesyanol C (4) with an IC50 1802,3; 4840,0; 61,8 and 425,5 mg/ml respectively. Hopeaphenol (3) showed more active than vitamin C (IC50 83,9 mg/ml) and BHT (1328,1mg/ml)